Developing strategies for improving the quality and performance of clinical contraceptive services : a review - Karim, Ali Mehryar; Khan, Md. Shamsul Islam (ICDDR,B special publication ;, 1999)
Study conducted at Abhoynagar and Mirsarai upazilas of Bangladesh.